Selective area deposition of diamond films on AlGaN/GaN heterostructures. Issue 12 (26th August 2014) - Izak, Tibor; Babchenko, Oleg; Jirásek, Vít; Vanko, Gabriel; Vallo, Martin; Vojs, Marián; Kromka, Alexander
<x xml:space="preserve">Abstract</x> Diamond‐on‐GaN heterostructure is a promising hybrid material system with a variety of applications such as heat spreaders, high‐temperature, and high‐power devices. From a practical point of view, polycrystalline diamond is shown to be an attractive solution to the limited use of the expensive monocrystalline diamond substrates. Here we present selective area diamond deposition on AlGaN/GaN layers focusing on the elimination of surface and metal contact damage (Ni, NiO, Ir, and IrO2) and suppressing the spontaneous nucleation of diamond. Metal contacts are important for further applications such as diamond‐coated GaN based electronic devices. The growth of diamond films was performed by microwave chemical vapor deposition in different gas mixtures with the addition of CO2 or N2 to CH4/H2. Adding CO2 resulted in polycrystalline (PCD), while adding N2 led to the formation of nanocrystalline diamond film (NCD). The diamond deposition was carried out using selective area nucleation in a three‐layer sandwich structure (polymer/seeding layer/polymer), which avoided damage to the electrode and GaN surfaces from ultrasonic seeding by diamond particles. No protective layer was used on the GaN surface before diamond deposition, i.e., diamond films were grown directly on the AlGaN/GaN heterostructures. In the case of NCD deposition, no surface damaging of GaN was observed. For both NCD and PCD films, increasing methane from 1% to 2% in H2 minimized the surface damage of GaN films.